Oleuropein or rutin consumption decreases the spontaneous development of osteoarthritis in the Hartley guinea pig. Issue 1 (January 2015) - Horcajada, M.-N.; Sanchez, C.; Membrez Scalfo, F.; Drion, P.; Comblain, F.; Taralla, S.; Donneau, A.-F.; Offord, E.A.; Henrotin, Y.
Summary: Objective: To assess the potential protective effects of three polyphenols oleuropein, rutin and curcumin, on joint ageing and osteoarthritis (OA) development. Design: Sixty 4-week-old Dunkin–Hartley guinea pigs were randomized into four groups and received daily during 31 weeks either standard guinea pig diet (control group) or a standard guinea pig diet enriched with oleuropein (0.025%), rutin (0.5%) or rutin/curcumin (0.5%/0.25%) association. Biomarkers of OA (Coll2-1, Coll2-1NO2, Fib3-1, Fib3-2, ARGS), as well as inflammation prostaglandin E2 (PGE2 ) were quantified in the serum. Histological assessments of knee cartilage and synovial membrane were performed at week 4 (five young reference guinea pigs) and week 35. Results: At week 35, guinea pigs in the control group spontaneously developed significant cartilage lesions with mild synovial inflammation. The histological scores of cartilage lesions and synovitis were well correlated with the increased level of serum biomarkers. Histologically, all treatments significantly reduced the cartilage degradation score ( P  < 0.01), but only oleuropein significantly decreased the synovial histological score ( P  < 0.05) and serum PGE2 levels ( P  < 0.01) compared to the control group. Coll2-1 was decreased by rutin and the combination of rutin/curcumin, Fib3-1 and Fib3-2 were only decreased by the rutin/curcumin mixture, while Coll2-1NO2 was significantly decreased by all treatments ( P  < 0.05). Conclusion: Oleuropein and rutin ± curcumin significantly slowed down the progression of spontaneous OA lesions in guinea pigs. While no additive effect was seen in the curcumin + rutin group, the differential effects of oleuropein and rutin on inflammatory and cartilage catabolic markers suggest an interesting combination for future studies in OA protection.